The Dragon in the News : how Malawian journalists perceive the political influence of China on news reporting in Malawi - Nyirongo, Mwaona (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies)
The arrival of China in Malawi has been characterised by a growing sense of uncertainty where academics and social commentators at large have expressed concern over the intentions of the super power in the country. There are fears that China would like to extend its influence to Malawi as part of a broader push, to have greater influence in global politics and economics. That push is in part exercised through the media. The thesis examined the perception of Malawian journalists on how news media reports on Chinese activities in Malawi. It used content analysis to understand how the mediascape had changed from 2001 "“ 2007 when China had not established diplomatic relations with Malawi, and January 2008 "“ 2020 when China had established diplomatic relations. The thesis examined these shifts in journalistic representations of China in Malawi and developed prompts and probes from which journalist interviews were conducted. From the content analysis, it appears there is a remarkable change in the way China has been covered from 2001 "“ 2020. From 2001 "“ 2007, Malawian media, especially The Daily Times, was very harsh on China, uncritically reproducing Western representations of China as an aggressive country with no respect for human rights and dignity. This changed after January 2008 when the media leaned towards tolerance and acknowledgement of Chinese activities. Through interviews, journalists have indicated that the Chinese government offers opportunities, such as scholarships, fellowships, and exchange visits to journalists, making it difficult for them to bite the finger that is feeding them. This 'soft power' is backed up by the repressive power of the Malawi government, which uses intimidation to force journalists to report in their favour, thereby helping create a positive picture for China in Malawi. Journalists report that the significant shifts in journalistic representations of China have been mirrored by changes in the conceptualisation of journalistic roles in Malawi's mediascape.
Keywords: Journalists -- Malawi; Journalism -- Malawi; Journalism -- Political aspects -- Malawi; Journalism -- Objectivity -- Malawi; China -- Foreign economic relations -- Malawi; Malawi -- Economic conditions; Malawi -- Politics and government